2018
DOI: 10.3390/su10082783
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Research on the Key Success Factors of Marketing Ugly Fruits and Vegetables

Abstract: According to the 2011 research report of the Food and Agricultural Organization (FAO) of the United Nations, one-third of the world's edible fruits and vegetables are wasted every year, totaling about 1.3 billion metric ton. A source of such waste is ugly fruits and vegetables, which have the same nutritional value as that of normal fruits and vegetables, but are discarded due to poor appearance for selling. If consumers can rediscover their value, it will be one of the ways to change food waste. This study fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Many researchers have called for the re-education of consumers on foods' natural variability in appearance, food quality, and on the validity and edibility of "ugly" foods (Loebnitz et al, 2015;Louis & Lombart, 2018;Helmert, Symmank, Pannasch, & Rohm, 2017;de Hooge et al, 2018;Tu et al, 2018). If consumers are exposed to information on "ugly" foods that will change their preconceptions of food quality and taste based on appearance properties, then it is possible that consumers will one day judge "ugly" foods equally to conventionally beautiful foods.…”
Section: Literature Review the Issue Of Food Wastementioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have called for the re-education of consumers on foods' natural variability in appearance, food quality, and on the validity and edibility of "ugly" foods (Loebnitz et al, 2015;Louis & Lombart, 2018;Helmert, Symmank, Pannasch, & Rohm, 2017;de Hooge et al, 2018;Tu et al, 2018). If consumers are exposed to information on "ugly" foods that will change their preconceptions of food quality and taste based on appearance properties, then it is possible that consumers will one day judge "ugly" foods equally to conventionally beautiful foods.…”
Section: Literature Review the Issue Of Food Wastementioning
confidence: 99%
“…Increasing awareness among consumers of environmental sustainability issues and the issue of food waste in relation to "ugly" foods has been argued to be potentially effective as a part of the marketing strategies used to sell "ugly" foods. Tu et al (2018) argue that "if consumers understand the relevant [environmental] issues and pay attention to the truth of vegetable and fruit production, they can use their consumption power to protect their own and environmental rights" (p. 1). Tu et al (2018) urge grocers and food retailers to advocate the concept of food waste, to advocate the importance of environmental protection, and to link environmental sustainability education and advocacy to an innovative brand story for "ugly" fruits and vegetables (p. 21).…”
Section: The Marketing Of "Ugly" Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…508-509). Tu, Lee, and Wei (2018) define "ugly" fruits and vegetables as "crops that do not meet purchasing conditions because of poor appearance, defective appearance" and abnormalities in shape and in size (p. 2). "Ugly" foods are also commonly known as "aesthetically imperfect," "wonky" (Porter et al, 2018, p. 869), "off-grade," "Not Good" (NT) (Tu et al, 2018, p. 2), "abnormal," "suboptimal," and "inferior" produce (Jaeger, Machín, Aschemann-Witzel, Antúnez, Harker, & Ares, 2018, p. 17).…”
Section: Literature Review the Issue Of Food Wastementioning
confidence: 99%
“…Tu et al reported "Analysis and Research on the Key Success Factors of Marketing Ugly Fruits and Vegetables" [34]. This study first explored related topics of food waste through the literature; then it drew up an interview outline, obtained and ranked the key success factors for the evaluation indices through education and interviews with industry professionals, and summarized the key success factors of marketing ugly fruits and vegetables through questionnaire and experts interview perspectives that targeted consumer groups as the questionnaire respondents.…”
Section: Tu Et Al Reported "Key Factors Of Sustainability For Smartpmentioning
confidence: 99%